IDENTIFIKASI KUALITAS DEDAK YANG DISIMPAM DALAM BERBAGAI JENIS KEMASAN - Maulia Ramahariah; Farida Fathul; Liman . (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
Rice bran is by product from rice milling and feed is one that is difficult to dry so provision when stored in large quantities with special packaging. Information about packaging materials has not been known. The purpose of this study was to determine the quality of bran that is stored in various types of packaging and determine the best packaging in storage. This study used completely randomized design followed by Least Significant Difference test. The variables measured were organoleptic and chemical testing. The results showed that a various packaging used in storage of rice bran for 6 weeks was significantly effect (P<0,05) to the texture, moisture content, and peroxide value, but were not significantly effect (P>0,05) to colour, odor, and the rate of fat rice bran.  In addition, position sampling in packaging for 6 weeks were not significantly effect (P>0,05) to colour and the texture, but was significantly effect (P<0,05) to odor of rice bran. Then white plastic packaging as the best in maintaining the quality of rice bran.   Keyword: Rice bran, Types of Packaging, Peroxide Number